The view of teachers on bullying and implications for nursing - Marta Angélica Iossi Silva; Jorge Luiz da Silva; Beatriz Oliveira Pereira; Wanderlei Abadio de Oliveira; Marcelo Medeiros (SciELO, 2014)
Objective: To understand school bullying from the perspective of teachers and reflect about the possible actions of the health area when coping with it. The guidelines of the School Health Program of the Ministries of Health and Education were used to reach that purpose. Method: A qualitative study carried out with teachers of a public school in Minas Gerais. Focus groups were used to collect data and the empirical material was decoded from thematic analysis of content, resulting in an analytical category: conceptions and experiences of teachers on bullying. Results: Specific perceptions about the phenomenon and the use of ineffective intervention resources were identified. In the interpretive plan were problematized the health and nursing contributions with resizing the interventions and the continuing training process of teachers. Conclusion: The results point to the construction of intersectoral practices for coping with bullying.